Introductory stochastic analysis for finance and insurance - Lin, X. Sheldon (Wiley series in probability and statistics., 2006)
Aimed at actuaries who would like to learn stochastic modeling techniques, this is an introductory level book on stochastic analysis for finance. It introduces the basic theories of stochastic processes and stochastic calculus, and provides the tool kits for modeling and pricing in finance and insurance.